Clinical and Psychological Features of Minor Victims of Cybergrooming - E.V. Nutskova; E.G. Dozortseva (Психология и право, 2022)
In order to identify the risk factors of victimization and determine the clinical and psychological consequences of cybergrooming for underage victims, a pilot study was conducted. 40 underage girls aged from 8 to 18 years, victims of sexual abuse on the Internet, were examined. The state of various spheres of mental activity and the state of victims were retrospectively assessed at the time before they entered into communication with the offender, features of the criminal situation were studied, the consequences of violence and suffered abuse were identified and analyzed. The diagnostic complex included methods and techniques aimed at studying cognitive functions, individual characteristic and behavior. The method of studying documents (medical documentation, criminal case materials, including Internet correspondence of victims and offenders) was also used in the work. Statistical processing of the results was carried out by methods of descriptive statistics. Risk factors for girls to become a victim of cybergrooming were identified, and the immediate clinical and psychological consequences of abuse were described. Prospects for further research are described.